Fenomenologi Gaya Busana Muslimah Terhadap Etika dan Estetika Berbusana di Kalangan Mahasiswa - Dwi Meilasari, Retno Desti; Butar-Butar, Khairunnisa Desti; Hasibuan, Elfi Husnita; Humaidah, Tri Anisah; Siagian, Ruri Annisa (-, 2026)
The phenomenon of wearing Muslim clothing among Muslim women indicates either a high level of religious awareness or merely following fashion trends, which in this case can be understood that Muslim clothing should cover the body of Muslim women except for the face and hands. This study aims to identify the issues concerning ethics and aesthetics in Muslim attire. In addition, it seeks to understand the moral values and norms in the awareness of ethical dressing. This study uses a descriptive qualitative research method. It employs phenomenological study and interview analysis, in which the researcher collected data from interviews with 60 students from the Faculty of Business and Applied Sciences. The results of this study highlight the importance of ethics and aesthetics in Muslim dressing for the younger generation in the present era, to prevent discrepancies in the norms of proper attire. Students' understanding of Muslim dress ethics is still varied, with some students viewing Muslim attire as a religious obligation that must comply with Islamic law, while others place more emphasis on aesthetic aspects such as trends, styles, and visual appearance. Moral and ethical awareness in Muslim dressing is not formed instantly, but through a process of education, value internalization, and continuous habituation.